PUZZLES INVOLVING THE STOCK MARKET, INFLATION AND THE PREDICTABILITY OF STOCK MARKET RETURNS - Turanboyev Boburjon Qodirjon o'g'li; Rajabboyev Botirjon Odil o’g’li (QO‘QON UNIVERSITETI XABARNOMASI, 2022)
The need for stock market is rising in the modern day. Particularly, there is growing interest in companies with high share prices. However, the danger also rises as the interest does. There are several reasons for this. In other words, inflation is one of the largest risk concerns. Inflation control is a national issue, not just a business issue. Research on this subject was done by scientists including Thomas C. Chiang, Amal Essayem Sakir, Gormus Murat Guven, and Pierlauro Lopez. However, they haven't done enough study on how to predict inflation and how much it affects the stock market. The stock market, inflation, and the predictability of stock market returns are all topics that are clarified in this article.